Dušan Čkrebić, The Comintern. Turbulent Events and Their Consequences for the SFRY and Serbia - Rastović, Aleksandar P. (Sociološki pregled, 2019)
The text is a critical review of the study written by Dusan Čkrebić, the last living highest party and state ofcial of the SFRY and Serbia, on the role of the Comintern, the CPY and Josip Broz Tito in the breakdown of Yugoslavia. The author’s main thesis is that the foundations of the breakdown of Yugoslavia were laid at the Fourth Congress of the CPY in Dresden in 1928, in line with the Comintern directive. In the book, the author also presents his role in the attempt of the state leadership of Serbia in 1977 to amend the Constitution of 1974, which proclaimed the autonomous provinces of Kosovo and Vojvodina as constitutional elements of the federation.Keywords: Josip Broz Tito, Yugoslavia, Comintern, Communist Party of Yugoslavia, Blue Book, Serbia, 1974 Constitution.